Divergent effects of education and occupation history on age at onset within Alzheimer's and frontotemporal dementia: Neuropsychiatry and behavioral neurology: Novel risk factors and novel approaches to risk in dementia. (7th December 2020) - Miller, Zachary A.; Allen, Isabel Elaine; Neylan, Kyra D.; Diggs, Ryan T.; Bogely, Rian L.; Palser, Eleanor; Perry, David C.; Brown, Jesse; Sturm, Virginia; Rabinovici, Gil D.; Rosen, Howard J.; Kramer, Joel H.; et al.
Abstract: Background: Cognitive reserve refers to the resilience education and life‐time mental activity confer against neurodegenerative disease. Mostly understood within Alzheimer's disease (AD), we investigated the impact education and occupation history have within frontotemporal dementia (FTD). Methods: Employing the United States Bureau of Labor Statistics (USBLS) job classification, we screened occupation histories in all participants who presented to the UCSF MAC from 1998‐2019 and met criteria for FTD (n=638; including behavioral variant FTD, semantic variant primary progressive aphasia, and nonfluent variant primary progressive aphasia) and compared to a sample of AD matched for age at symptom onset (n=600). Results: Compared to AD, FTD possessed significantly higher amounts of years of education (15.7±2.9 vs. 15.3±3.5, p =0.03) and male sex (50.2% vs. 43.7%, p =0.02). Adjusting for these differences, seven of 23 USBLS categories differed between AD and FTD (Table 1). "Architecture & Engineering, " "Computer & Mathematical, " and "Life, Physical, & Social Science, " which together constitute the STEM (Science, Technology, Engineering, and Mathematics) professions, were increased in FTD. "Arts, Design, Entertainment, Sports, & Media, " "Personal Care & Services, " "Production, " and "Other" occupation categories were increased in AD (referred to here as AD‐Relevant). STEM occupations predict FTD over AD (OR, 2.3; 95% CI, 1.7 to 3.2), whereas AD‐Relevant occupations predict AD over FTD (OR, 2.2; 95% CI, 1.6 to 3.1). Survival curve analyses of STEM vs. AD‐Relevant vs. all remaining occupations revealed that STEM occupation associates with earlier symptom onset in FTD and later onset in AD and AD‐Relevant careers, the opposite. Furthermore, within FTD, disease duration was longest in the STEM cohort compared to all remaining and AD‐relevant careers (11.4 vs. 8.9 vs. 9.3, p =0.003). Conclusions: We find that education and occupation history impact age at symptom onset within AD and FTD, in opposing manner. The cognitive reserve hypothesis was created to explain the delayed symptom onset and shortened disease duration increased years of education and occupational complexity bestow on individuals with AD. Within FTD, we observe the opposite ‐ earlier symptom onset and greater disease duration in STEM professionals ‐ suggesting a reciprocal process may be at work within FTD.